RANCANG BANGUN SISTEM KONTROL DAN MONITORING SUHU PADA RUANG FREEZER BERBASIS ESP8266 (STUDI KASUS PADA PT. AEROFOOD ACS DENPASAR) - Dody Pramudya Indra Jaya, Komang; Dyana Arjana, I Gede; Suartika, I Made (Jurnal SPEKTRUM; Vol 10 No 2 (2023): Jurnal SPEKTRUM, 2023)
The temperature control and monitoring system in the freezer room has an important role in maintaining the quality of food raw materials. Freezer space is used to store food raw materials to keep them fresh and undamaged. However, if the temperature in the freezer compartment is not properly monitored, food raw materials may be damaged which can affect their quality and safety. Therefore, an IoT-based temperature control and monitoring system in the freezer room was created using Wemos D1 R2. The design of this prototype uses hardware, namely the WeMos D1 R2 microcontroller based on ESP8266 because it can be connected to WiFi, DHT22 temperature sensor, I2C LCD and relay. The results of this prototype design are being able to read the temperature and humidity of the freezer room and having a temperature control system that can be seen on the Blynk application on a smartphone by displaying the temperature and humidity values. The conclusion from this study is that the prototype has succeeded in controlling the temperature of the freezer room as well as monitoring the temperature and humidity of the freezer room and displaying it on the Blynk application on a smartphone and has a warning notification when the temperature rises above -18 degrees celsius.